2000
DOI: 10.1007/s004240000335
|View full text |Cite
|
Sign up to set email alerts
|

Body fluid regulation in µ-gravity differs from that on Earth: an overview

Abstract: Similar to the response to central hypervolemic conditions on Earth, the shift of blood volume from the legs to the upper part of the body in astronauts entering µ-gravity should, in accordance with the HenryGauer mechanism, mediate diuresis and natriuresis. However, fluid balance and kidney function experiments during various space missions resulted in the surprising observation that the responses qualitatively differ from those observed during simulations of hypervolemia on Earth. There is some evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 28 publications
(56 reference statements)
3
26
0
Order By: Relevance
“…In addition, the effects of the muscular metaboreflex on blood pressure and heart rate are enhanced after space flight both during isometric contractions (Fu et al 2002) and during dynamic exercise (Iellamo et al 2006). Therefore, since the modification of blood distribution obtained during HDTBR overlaps that observed in real microgravity (Convertino 1996), we may hypothesise that a larger and more effective metaboreflex may have helped maintain a normal pressure response during exercise also in the present condition, although the mechanisms underlying the loss of body fluid may be different in the two conditions (Drummer et al 2000).…”
Section: Discussionmentioning
confidence: 59%
“…In addition, the effects of the muscular metaboreflex on blood pressure and heart rate are enhanced after space flight both during isometric contractions (Fu et al 2002) and during dynamic exercise (Iellamo et al 2006). Therefore, since the modification of blood distribution obtained during HDTBR overlaps that observed in real microgravity (Convertino 1996), we may hypothesise that a larger and more effective metaboreflex may have helped maintain a normal pressure response during exercise also in the present condition, although the mechanisms underlying the loss of body fluid may be different in the two conditions (Drummer et al 2000).…”
Section: Discussionmentioning
confidence: 59%
“…This was measured mainly by the reduction in plasma norepinephrine levels observed in these models 42,43,48–51 . However, renal plasma flow (RPF), glomerular filtration rate (GFR), and urine production were shown to be unchanged in space, 39,52,53 contrary to previous data from simulated microgravity models that suggested increased GFR and diuresis 35 . Instead of increased natriuresis, an increased sodium reabsorption was observed in flight, 31 resulting in a positive sodium balance (Figure 2).…”
Section: Physiological Changes During Space Flightmentioning
confidence: 70%
“…But, several space missions have shown that conclusions drawn from HDBR studies are not totally transferable to space. It has been shown in the MIR-92-, D2-, SLS-1/SLS-2 missions that no diuresis occurred in astronauts when entering microgravity (Drummer et al 1993;Drummer et al 2000a;Leach et al 1996). Pre-mission treatment like sauna sessions, decreased fluid intake and application of diuretics might support these findings of balanced fluid homeostasis at the beginning of spaceflight.…”
Section: Body Fluid Regulation In Bed Restmentioning
confidence: 76%